The Poetics of Language and Writing Spaces in Al-Ayyam by Taha Hussein - baadach, Nasser (El Omda in Linguistics and Discourse Analysis, 2019)
This research paper attempts to address certain language-related questions concerning the spaces of novelistic writing, as exemplified in Taha Hussein’s Al-Ayyam. The author strives each time to fill reality with the force and necessity of language. Since space in the text is inherently related to the space of reality, every language occupies a specific space; thus, every discourse conveys something about a particular space. From this perspective, questions arise: What is language? Has it been able to express the author’s real-world space truthfully? What are the spaces of writing? Do the places in the novel reflect the spaces the author intended, or not? Was the author’s space a prison among prisons, or not? In addressing these issues, we will adopt a descriptive-analytical approach to examine them from all angles.